Study Of The Transformation Of Shanghai Fangyun Guangang From Warehousing To Third Party Logistics - Li, Y, Yi Qing (2008)
This thesis conducts a study on how a traditional strorage enterprise is transformed into a Third Party Logistics(3PL) service provider.